2019
DOI: 10.1155/2019/4506303
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNA Let-7 from Menstrual Blood-Derived Endometrial Stem Cells Alleviates Pulmonary Fibrosis through Regulating Mitochondrial DNA Damage

Abstract: Idiopathic pulmonary fibrosis (IPF) is a prototype of chronic, progressive, and fibrotic lung disease with high morbidity and high mortality. Menstrual blood-derived stem cells (MenSCs) have proven to be an attractive tool for the treatment of acute lung injury and fibrosis-related diseases through immunosuppression and antifibrosis. However, whether MenSC-derived exosomes have the similar function on pulmonary fibrosis remains unclear. In the present study, exosomes secreted from MenSCs (MenSCs-Exo) were veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 48 publications
3
62
0
Order By: Relevance
“…Of the 4,925 titles and abstracts screened, 233 articles were reviewed, 90 were assessed for eligibility and 39 were included in the final analysis (Figure 2) [31–69]. The selected studies were published between 2014 and 2020 and included in vitro, ex vivo , and in vivo studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 4,925 titles and abstracts screened, 233 articles were reviewed, 90 were assessed for eligibility and 39 were included in the final analysis (Figure 2) [31–69]. The selected studies were published between 2014 and 2020 and included in vitro, ex vivo , and in vivo studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In studies modelling pneumonia, EVs induced adaptive immunity and reduced bacterial load [67]. Studies that tested EVs on models of pulmonary fibrosis reported that EV treatment reduced collagen deposition and density, halted fibrosis progression by inhibiting myofibroblast differentiation, and improved the Ashcroft score, a standard scoring system for pulmonary fibrosis [32,43,50,65].…”
Section: Resultsmentioning
confidence: 99%
“…Current studies focus on the extracellular vesicles mainly isolated from human blood, or, respectively, serum or plasma [ 71 , 72 , 73 , 74 ]. However, extracellular vesicles can be isolated from a broad variety of human body fluids such as urine [ 75 , 76 ], saliva [ 77 , 78 ], bronchoalveolar liquid [ 79 ], pleural lavage [ 80 ], and cerebrospinal fluid [ 81 ] and even more uncommon ones like tears [ 82 ], semen [ 83 ], menstrual blood [ 84 ], peritoneal lavage [ 85 , 86 ], bile [ 87 ], and pancreatic juice [ 88 ]. An overview of non-coding RNAs that were analyzed in extracellular vesicles isolated from different liquid biopsies of different kinds is presented in Table 1 .…”
Section: Characterization and Importance Of Extracellular Vesicle mentioning
confidence: 99%
“…BMSCs promote an immunoregulatory, anti-inflammatory monocyte phenotype to prevent PF (Mansouri et al, 2019). Exosomal let-7 from menstrual blood-derived endometrial stem cells alleviates lung fibrosis and alveolar epithelial cell damage in mice by regulating reactive oxygen species levels, mitochondrial DNA damage and NLRP3 inflammasome activation (Sun et al, 2019). Lung fibroblast-derived EVs from IPF patients were shown to increase mitochondrial reactive oxygen species levels and associated mitochondrial damage in lung epithelial cells, and these EVs were sown to contain elevated levels of miR-23b-3p and miR-494-3p (Kadota et al, 2020).…”
Section: Novel Mechanisms Of Pf Mediated By Exosomesmentioning
confidence: 99%